Bacterial contamination in milk kitchens in pediatric hospitals in Salvador, Brazil - Romilda Castro Cairo; Luciana Rodrigues Silva; Carol Ferreira de Andrade; Maria Goreth de Andrade Barberino; Antônio Carlos Bandeira; Kleber Pimentel Santos; Daniel R. Diniz-Santos (Brazilian Journal of Infectious Diseases)
Milk may represent an important source of infectious agents to hospitalized pediatric patients. To describe the bacterial microflora isolated from the hands, stools, pharynx of all workers at milk kitchens in pediatric hospitals in the city of Salvador, Brazil, as well as in the formulas prepared by them, we carried out this cross-sectional study with all 91 workers from the 20 milk kitchens of all the public and private hospitals in Salvador, Brazil. Hand and pharynx swabs and stool samples were collected from all workers, as well as samples of the milk and formulas delivered by the kitchens. All samples were cultured for the detection of pathogenic and non-pathogenic bacteria. Pathogenic bacteria were isolated from 20 (22.0%) and 8 (8.8%) cultures of the hands and pharynx of the workers, respectively. No pathogenic bacteria were isolated from stool samples. Pathogenic bacteria were isolated from 17 (18.7%) milk samples. The prevalence of pathogenic bacteria in hand swabs was significantly higher in workers from public (37.8%) than from private (6.5%) hospitals (prevalence ratio [PR]=5.8; p<0.01). Pathogenic bacteria were isolated from two (4.4%) workers from public hospitals and six (13.0%) workers from private hospitals (PR=0.38; p=0.27). Pathogenic bacteria were isolated from 11 (24.4%) milk samples from public hospitals and 6 (13.0%) from private hospitals (PR=1.9; p=0.16). A high prevalence of contamination was found, mainly on the hands of workers on units for manipulation of milk. Preventive efforts should be intensified and focus primarily on effective hand washing and continuous work supervision.